(untitled) (Revista Brasileira de Plantas Medicinais, 2025)
Aloysia gratissima is well known as “Mimo do Brasil” in the Brazilian folk medicine and the infusion of its branches and twigs is an important analgesic used against stomached and bladder pains. However, few investigations about specific and efficient eluent systems applied for the purification of its essential oil have been reported. Essential oil extracted from dried leaves was obtained by hydrodistillation using a Clevenger apparatus. The isolation of cis-pinocarveyl acetate and trans-pinocamphone compounds were performed by Column Liquid Chromatography (CLC) through a number of appropriate solvent systems used as mobile phase. Results have showed that isolation of cis-pinocarveyl acetate and trans-pinocamphone were possible using, respectively, ethyl acetate/hexane 1:59 (v/v) and 1:5 (v/v) as solvent systems. Therefore, the aims of this work were to provide the ideal solvent systems for the isolation of important compounds from Aloysia gratissima essential oil using Column Liquid Chromatography (CLC) as well as identify them from GC retention indices, relative to C6-C24 n-alkanes, by comparison of their MS spectra with those reported in the literature (Adams 1995) and by computer matching with the NBS-Reve mass spectra library.